2019
DOI: 10.1016/j.strusafe.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic sensitivity analysis of offshore wind turbines using a transformed Kullback-Leibler divergence

Abstract: Characterizing uncertainty in complex systems is steadily growing as a topic of interest. One of the efficient ways to characterize a complex system is achieved by probabilistic sensitivity analysis. In the context of performing it, there are a limited number of methods to quantify the change of the output to its full probabilistic extent. Moreover, in some engineering applications, such as reliability analysis, some established indicators of sensitivity do not fit the best interest of the analysis. This is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…MC in WRA is usually used for windfarm layout optimization 23,24 or profitability UA 10,[25][26][27][28][29] often with no SA accompanying. In wind turbine specific studies, MC was also used for stochastic blade flutter analysis, 30 turbine reliability, 31 and fatigue load 32,33 assessments. To the best of the authors' knowledge, SA in WRA commonly uses OAT methods [10][11][12][13][14][15] that disregard model nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…MC in WRA is usually used for windfarm layout optimization 23,24 or profitability UA 10,[25][26][27][28][29] often with no SA accompanying. In wind turbine specific studies, MC was also used for stochastic blade flutter analysis, 30 turbine reliability, 31 and fatigue load 32,33 assessments. To the best of the authors' knowledge, SA in WRA commonly uses OAT methods [10][11][12][13][14][15] that disregard model nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…The observed coincidence deserves further theoretical and numerical studies, especially in the context of material and geometrical structural nonlinearities [ 38 , 39 ] with some stochastic imperfections. Further comparison of Bhattacharyya relative entropy with other probabilistic divergency models such as Kullback-Leibler [ 40 ], for instance, may provide an interesting alternative to the existing FORM and SORM reliability algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Hübler et al 5 Robertson et al 9 Toft et al 11 Teixeira et al 8 Peeringa &Bedon 4 Velarde et al 6 Turbine size (MW) studies regarding either the parameters considered, or the parameters identified as important. This may be caused both by different sensitivities for different turbines and foundations, as well as by the level of uncertainty assumed in the studies.…”
Section: Referencementioning
confidence: 99%
“…3 These parameters should be given particular focus during the design process, and they can be identified through a sensitivity analysis (SA). Numerous SAs and reliability studies have been performed on individual OWTs, [4][5][6][7][8][9][10][11][12][13][14] with size varying from 4 to 10 MW. The results from selected studies considering several uncertain parameters are summarised in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation